PENGARUH KEPEMIMPINAN, KOMPETENSI DAN KOMITMEN TERHADAP PRESTASI KERJA PEGAWAI DINAS KOPERASI, USAHA MIKRO KECIL DAN MENENGAH KABUPATEN POLEWALI MANDAR - Amrullah, Mustajab (Siddiq Institute, 2022)
This study aims to test and prove empirically: (1) are the leardership influence onÂ the work achievement employee; (2) are the competence influence onÂ the work achievement employee; and (3 are the individual commitment influence onÂ the work achievement employee; Theoretically, this research is expected to enrich and complement the knowledge in the field of human resource management so as to be useful to academics and practitioners. The type of research is explanatory research, population and sample in the study were 48 employees. The samples using total sampling technique, were analyzed by linear regression analysis with software SPSS 23. The results showed that (1) Leadership affect the work performance of employees, each employee has a character that berkemimpinan though not always dominant, but with the character of leadership, employees were able to manage themselves even coworkers. Leadership will exert yourself and co-workers to be creative, innovative, initiative and responsibility for his performance. The attitude of leadership is also able to bring work performance had been previously envisioned .; (2) Competence affect the work performance of employees, competences of the employees in the form of knowledge to the job, the level of mastery of skills and work discipline, proven to improve employee job performance. Indicators of knowledge provides the highest influence to increase employee job performance; (3) The commitment of individuals affect the work performance of employees, employee-owned individual commitments which will foster a passion for achievement on employees in these establishments. With a strong commitment of the employees will adopt a strategy for achieving employee beprestasi predicate.